An approach to support collaborative ontology construction - Tahar, Kais; Kücherer, Christian; Paech, Barbara (Exploring complexity in health, 2016)
This paper presents an ontology modeling approach based on Excel2OWL, a self-developed tool which efficiently supports domain experts in collaboratively constructing ontologies from textbooks. This approach was applied to classic IM textbooks, resulting in an ontology called SNIK.